2021
DOI: 10.3389/fnano.2020.621681
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Active Free Direct Optical Sensing of Aflatoxin B1 and Ochratoxin A Using a Manganese Oxide Nano-System

Abstract: Aflatoxins-B1 (AFB1) and Ochratoxin-A (OchA) are the two types of major mycotoxin produced by Aspergillus flavus, Aspergillus parasiticus fungi, Aspergillus carbonarius, Aspergillus niger, and Penicillium verrocusumv. These toxins are mainly found in metabolite cereals, corn, coffee beans, and other oil-containing food items. Excessive consumption of these toxins can be carcinogenic and lead to cancer. Thus, their rapid testing became essential for food quality control. Herein, manganese oxide nanoparticles (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The limit of detection (LOD) 45 was determined to be 2.54 ng mL −1 by applying eqn (iv):LOD = 3 σ b / m where σ b and m represent the standard deviation of the intercept and the slope of curve, respectively. The obtained LOD is much lower than that of Fe 3 O 4 /GO 46 and MnO 2 47 based biosensors reported so far. A comparative investigation of the biosensing parameters of existing nanobiosensors for AFB1 detection and the current work is displayed in Table 1.…”
Section: Resultsmentioning
confidence: 56%
“…The limit of detection (LOD) 45 was determined to be 2.54 ng mL −1 by applying eqn (iv):LOD = 3 σ b / m where σ b and m represent the standard deviation of the intercept and the slope of curve, respectively. The obtained LOD is much lower than that of Fe 3 O 4 /GO 46 and MnO 2 47 based biosensors reported so far. A comparative investigation of the biosensing parameters of existing nanobiosensors for AFB1 detection and the current work is displayed in Table 1.…”
Section: Resultsmentioning
confidence: 56%
“…56 It was suggested that if a sample is showing response at 400 and 550 nm with respect to 365 and 730 nm excitation wavelengths, it is supposed to be contaminated with aflatoxins. Singh et al 57 also reported that aflatoxin B1 and ochratoxin A have maximum absorption (λ max ) at 365 and 380 nm. Both UV−visible and fluorescence spectroscopic techniques are easy to handle and cost-effective.…”
Section: Chromatographic Techniquesmentioning
confidence: 99%
“…22 Among the various nanomaterials such as ZnO, CuO, NiO, Mn 2 O 3 , CeO 2 , CeO 2 have been known to have excellent electrochemical properties. 15,[23][24][25][26][27] In our recently published paper, picogram level detection of Ochratoxin-A has been achieved using a ceria-based electrochemical microfluidic nanobiochip. 15 However, during the electrochemical study on the microfluidic chip, low current values were obtained.…”
mentioning
confidence: 99%